DESIGN IMPROVEMENT OF HEAVY VEHICLE JACK FOR SMALL AND MEDIUM-SIZED ENTERPRISES (SME’S) - DOLAH MUHAMAD, MOHD FARIZZAL (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
ABSTRACT – This research is an invention to help employee works on the tractor gearbox repair. Currently, the tractor gearbox repairing and assembling are a very difficult and complicated task. From the research, it carried out design a tool of tractor gearbox stand that can be used by mechanics in separation work and the inclusion of tractor gearbox. This stand is to facilitate workers to separating and re-assembling the gearbox on the tractor. This work is very difficult to implement as there is no special tool used in doing the works. Mechanics that do this work will use a lot of equipment like floor jack in performing this task. With the use of these tools, the risk of accidents is high. Safety issues during tractor gear separation proses are also noted. The risk of accidents while performing these works using the current way are high. This is because the separate tractors will be stored on the jack and the risk of falling during work is high. Tractor gearbox stand is a stand that can be adjusted forward and backward on the rolling base. It is to facilitate the separation process and the inclusion of tractor gearbox. It will be adjustable and run on the site provided. Works like power take off (PTO) maintenance, clutch conversion and so on can be done when the tractor has been raised on this tractor gearbox. Tractor gearbox stand is used exclusively for heavy machinery i.e. tractors. This project will implement a tool to facilitate the separation and re-assembly of tractor gear boxes, clutch conversion and power take off (PTO) maintenance. The project will also ease and simplify gearbox separation work. Lastly, this tool will minimize the use of workers to do work